HUBUNGAN STATUS GIZI DAN AKTIFITAS FISIK SIKLUS MENSTRUASI PADA REMAJA PUTRI DI SMPN 39 PEKANBARU - Nurhapipa, Nurhapipa; Nurlisis, Nurlisis (Ensiklopedia of Journal, 2024)
Adolescence is a transition period from childhood to physical adulthood. Adolescence is characterized by changes in physical appearance and biological functions, especially those related to the sexual glands. Menstrual disorders have a certain relationship to the physical and psychological condition of women. Menstrual disorders are influenced by body weight, frequency of exercise, physical activity, stress, diet, environmental exposure, working conditions, synchronization of the menstrual process, and endocrine disorders. General objective to analyze the relationship between nutritional status and physical activity on the menstrual cycle in adolescent girls at SMPN 39 Pekanbaru. This type of research is quantitative analytical with a cross sectional design. This research was conducted in August 2023. The research location was at SMPN 39 Pekanbaru. The population and sample are 100 teenagers attending SMPN 39 Pekanbaru (Total Sampling). Data analysis using univariate and bivariate analysis (chi square test) with 95% CI. The results of this study show that there is a relationship between physical activity with a p value of 0.014 (<0.05) and nutritional status with a p value of 0.008 (<0.05) with the menstrual cycle. There is a need for the role of teachers and health workers in improving adolescent health through the PKRR program.Keywords: Adolescents, Nutrition, Menstruation, SMPN 39